Cognitive Influences in Parkinson's Disease Patients and Their Caregivers: Perspectives From an Australian Cohort - Lubomski, Michal; Davis, Ryan L.; Sue, Carolyn M. (Frontiers in Neurology, 2021)
Objectives: Cognitive impairment impacts negatively on Parkinson's disease (PD) patient and caregiver quality of life (QoL). We examined cognitive impairment in PD patients and their caregivers to determine if caregiver cognition affected their PD relative. Methods: Validated cognition and clinical outcome measures were assessed in 103 PD patients and 81 caregivers. Results: PD patients showed more cognitive impairment than their carers, with 48.6% having possible Mild Cognitive Impairment (MCI) and 16.5% having PD dementia. Increasing age, male gender, lower education level, various non-motor symptoms and certain therapies, associated with poorer cognition in PD. Eighteen and a half percent of caregivers were found to have MCI, in association with a lower physical and mental QoL. This reflected in lower QoL and mood for the respective PD patients. Conclusion: Impaired cognition and QoL in caregivers was associated with decreased QoL and mood for respective PD patients, suggesting MCI in caregivers is an important consideration for the management of PD.